#TITLE_ALTERNATIVE# - ARYA SAKTI (NIM : 13204162); Pembimbing : Dr. Ir. Yusra Sabri S, JAKA
The dynamics of the primary energy sector has a significant influence on the electricity sector. This certainly affects the dynamics of electricity production costs and profit margins for investment on development. This study concerns on how is the long-term influence of primary energy dynamics in the electricity limited competition market system in Indonesia. Research conducted by modeling the dynamics of primary energy sector, particularly natural gas, petroleum, and coal, which affect the Indonesian electricity industry with a system dynamics approach. The factors considered are the use of energy mix, technological developments, changes in consumption growth, the discovery of new reserves, regulation, and substitution effects between primary energy. The main limitation is the model only takes into account the dynamics of primary energy in the domestic market, i.e. reserves and domestic demand, without the influence of international energy prices and foreign trade. Models are tested by comparing the simulation results with historical data for the year 1993-2003. From the test results, some parameters match the values and trend. Some are just match the trends in recent years only. Therefore, the model could still be used to see long-term effect of the above factors on the electricity industry. Simulation results show significant influence of the primary energy dynamics sector on the electricity industry. Electricity tariff of energy mix changes towards coal was lower than towards gas. Policy on primary energy sectors such as technology development, the decline in consumption growth, the discovery of new reserves, regulation of prices, and the substitution effect between the primary energy can reduce and restrain the rate of increase in electricity tariff. Each factor has different magnitude of effect on the tariff increase decline and slowdown. ItÃ‚Â’s depending on the magnitude of dynamic of primary energy factors.